Genome-Wide Association Studies Reveal Neurological Genes for Dog Herding, Predation, Temperament, and Trainability Traits - Shan, Shuwen; Xu, Fangzheng; Brenig, Bertram (Frontiers in Veterinary Science, 2021)
Genome-wide association study (GWAS) using dog breed standard values as phenotypic measurements is an efficient way to identify genes associated with morphological and behavioral traits. As a result of strong human purposeful selections, several specialized behavioral traits such as herding and hunting have been formed in different modern dog breeds. However, genetic analyses on this topic are rather limited due to the accurate phenotyping difficulty for these complex behavioral traits. Here 268 dog whole genome sequences from 130 modern breeds were used to investigate candidate genes underlying dog herding, predation, temperament and trainability by GWAS. Behavioral phenotypes were obtained from American Kennel Club based on dog breed standard descriptions or groups (conventional categorization of dog historical roles). The GWAS results of herding behavior (without body size as covariates) revealed 44 significantly associated sites within 5 chromosomes. Significantly associated sites on CFA7, 9, 10 and 20 were either located in or near neuropathological or neuronal genes including THOC1, ASIC2, MSRB3, LLPH, RFX8 and CHL1. MSRB3 and CHL1 genes were reported to be associated with dog fear. Since herding is a restricted hunting behavior by removing killing instinct, 36 hounds and 55 herding dogs were applied to analyze predation behavior. Three neuronal-related genes (JAK2, MEIS1 and LRRTM4) were revealed as candidates for predation behavior. The significantly associated variant of temperament GWAS was located within ACSS3 gene. The highest associated variant in trainability GWAS is located on CFA22, with no variants detected above the Bonferroni threshold. Since dog behaviors are correlated with body size, we next incorporate body mass as covariates into GWAS, and significant signals around THOC1, MSRB3, LLPH, RFX8, CHL1, LRRTM4 and ACSS3 genes were still detected for dog herding, predation and temperament behaviors. In humans these candidate genes are either involved in nervous system development or associated with mental disorders. In conclusion, our results imply that these neuronal or psychiatric genes might be involved in biological processes underlying dog herding, predation and temperament behavioral traits.